Probable Bruxism and Oral Health-Related Quality of Life - Mendiburu-Zavala, Celia Elena del Perpetuo Socorro; Naal-Canto, Aourumy Alessandra; Peñaloza-Cuevas, Ricardo; Carrillo Mendiburu, Josué (Odovtos - International Journal of Dental Sciences, 2021)
Bruxism is the habit of squeezing and grinding the dental organs (ODs), with dental contacts that have no purpose. The Oral Health-Related Quality of Life (OHRQoL) is defined as a multidimensional aspect that reflects the comfort of the individual in relation to their physiological and psychological functions, of the state of oral health. To determine the relationship between probable bruxism and OHRQoL in patients who came for care at the University Unit of Social Insertion (UUIS) of the Autonomous University of Yucatán (UADY), México from September 2019 to January 2020. Observational, analytical of case controls and cross-sectional. Two instruments were applied to 70 patients: the OHIP-EE-14 (validated by Castrejón-Pérez R.C., Borges-Yañez S.A.) and a questionnaire prepared by Mendiburu-Zavala C., based on Ordoñez Plaza et al., González-Emsoto et al., and De La Hoz-Aizpurua et al for the diagnosis of probable bruxism. Descriptive and inferential statistics were used. 47.1% (n=33) did present probable bruxism (CPB) and 52.9% (n=37) did not (SPB). The most frequent age group was 18-35 years old, with 67.2% (n=47), 34.3% (n=24) CPB. The most frequent circadian manifestation was waking with 49% (n=16). Those of CPB, a mean of 20.45±7.95 was obtained in the OHIP-EE-14 for the OHRQoL and SPB score, the mean was 7.81±4.84. There are statistically significant differences between CPB and SPB patients (p<.001). The probable bruxism does affect the OHRQoL level.